Gender, caste, & religious identities restructuring class in colonial Punjab - Malhotra Anshu (New Delhi Oxford Univ Press, 2002)
Description The book focuses on how the notion of being high caste , as it developed and transformed during the colonial period, contributed to the formation of a middle class among the Hindus and the Sikhs. While many reformist Sikhs and Hindus either d
Keywords: Castes; India; Punjab; Religious life; Social conditions; Social history; Women